2022
DOI: 10.3390/fire5030067
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Spontaneous Combustion Zones and Index Gas Prediction System in Goaf of “Isolated Island” Working Face

Abstract: Studies show that accurate division of spontaneous combustion (SC) zones in the goaf and the determination of the prediction system of the SC index are of great significance to prevent spontaneous and unwanted combustions in the goaf. Aiming at resolving the problem of coal SC in the goaf of an “isolated-island” fully mechanized caving face, a multiphysics model coupled with gas flow field and gas concentration field was established in the present study. Taking the 8824 working face of Nanzhuang coal mine as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Affected by factors such as mining, crustal stress, and CSC, the coal rock in goaf undergoes compression deformation and fracture, forming a caving zone, fracture zones, and curved subsidence zones in the vertical direction of the goaf [28,29]. The irregular arrangement of collapsed coal rocks and residual coal in the caving zone creates a specific void space under the influence of geology, mining, and coal rock properties.…”
Section: Permeability Evolution Of Goafmentioning
confidence: 99%
“…Affected by factors such as mining, crustal stress, and CSC, the coal rock in goaf undergoes compression deformation and fracture, forming a caving zone, fracture zones, and curved subsidence zones in the vertical direction of the goaf [28,29]. The irregular arrangement of collapsed coal rocks and residual coal in the caving zone creates a specific void space under the influence of geology, mining, and coal rock properties.…”
Section: Permeability Evolution Of Goafmentioning
confidence: 99%
“…Sun et al used three-dimensional CT reconstruction technology to extract the pore network structure of a coal sample and found that the injectivity and permeability of the heated coal samples were poor after nitrogen injection. Chai conducted a temperature-programmed experiment on coal and improved the prediction index gas system of SC, suggesting that CO and C 2 H 4 can be used as warning indicators for suspended solids in the gob. The scope of the “three zones” of spontaneous combustion can be comprehensively determined by the oxygen concentration, air leakage velocity, and temperature in the gob. , Through the coal spontaneous combustion experiment, Gui et al developed a method to determine the “three zones” of a gob using O 2 concentration through regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao Shankun proposed the synergistic anti-collision mechanism of a deep-hole roof presplitting blasting stress structure by analyzing the stress field of blasted rock mass, the plastic failure zone, and the stress and displacement change rules under different blasthole arrangements [18]. Chai Jiamei aimed to resolve the problem of coal SC in the goaf of an "isolated-island" fully mechanized caving face; a multiphysics model coupled with a gas flow field and a gas concentration field was established in the present study, and an accurate division of spontaneous combustion (SC) zones in the goaf and the determination of the prediction system of the SC index are developed [19]. lgor lvanovich Bosikov developed a generalized expression for the transfer functions of coalmine objects, taking into account delays, and carried out the method for managing the process of changing connections between devices (controllers-switches) of the technical system [20].…”
Section: Introductionmentioning
confidence: 99%